Expression of hypoxia‐inducible factor 1α, glucose transporter 1, and hexokinase 2 in primary central nervous system lymphoma and the correlation with the biological behaviors. Issue 8 (12th June 2020) - Shen, Na; Wang, Yaming; Sun, Xuefei; Bai, Xueyan; He, Jinglan; Cui, Qu; Qian, Jun; Zhu, Hong; Chen, Yuedan; Xing, Ruixian; Liu, Qing; Wu, Yuchen; et al.
Abstract: Background: It has been indicated that abnormal glucose metabolism mediated by hypoxia‐inducible factor 1α (HIF‐1α) played an essential role in the development of solid tumor. However, there were rare studies about the role of them in primary central nervous system lymphoma (PCNSL). Objective: To investigate the protein levels of HIF‐1α, glucose transporter 1 (GLUT1), and hexokinase 2 (HK2) in PCNSL and whether their levels are associated with prognostic factors. Methods: Expression of HIF‐1α, GLUT1, and HK2 in 39 tumor tissues was evaluated by immunohistochemical stainning. The correlation of the expression of HIF‐1α with the protein level of GLUT1 and HK2 was investigated. In addition, the association between these protein expression levels and clinical parameters and prognosis was analyzed. Results: In the tumor specimens of PCNSL, positive stainings of HIF‐1α, GLUT1, and HK2 were in 23 patients (58.97%), 25 patients (64.1%), and 26 patients (66.67%), respectively, which were associated with the expression level of lactic dehydrogenase (LDH), but not with age, gender, number of lesion, ECOG score, or deep structure. The expression of HIF‐1α was positively correlated with the expression of GLUT1 ( p  < .01, r  = .749) and HK2 ( p  < .01, r  = .787). Univariate analysis showed that upregulated GLUT1 was unfavorable predictors of progression‐free survival (PFS) in PCNSL. The results of Cox proportional hazards model showed GLUT1 was significantly associated with shorter PFS (hazard ration: 5.65; 95% confidence interval: 1.23–25.84; p  = .026). Conclusions: This study indicated that there was a hypoxic microenvironment and HIF‐1α was involved in the regulation of glycolysis pathway in PCNSL. GLUT1 might be a potential marker for shorter PFS in PCNSL. Abstract : There was a hypoxic microenvironment, and HIF‐1α was involved in the regulation of glycolysis pathway in PCNSL. GLUT1 might be a potential marker for shorter PFS in PCNSL.